Arabic Learning Methods in Saudi Arabia - Ainul Yakin; Banda Badri Mohammad Sokri (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
There are twenty-two countries that use Arabic as their mother tongue, and there are many non-Arab countries that learn the language, one of which is our country Indonesia. In schools in Saudi Arabia, the way they teach Arabic is different from the way they teach in Islamic boarding schools and schools in Indonesia, because of different methods in teaching. The focus of this research study is on the method of teaching Arabic spoken in Saudi Arabia. The research method used is a literature study approach (Libarary Reaseach). The results of the study concluded that in Saudi Arabia there are two types of schools, namely, International and Ahliyah schools whose teaching methods use slightly different Arabic teaching methods, where International schools use six methods, while Ahliyah schools use five Arabic learning methods.